RETRACTED ARTICLE: Long non-coding RNA SNHG16 reduces hydrogen peroxide-induced cell injury in PC-12 cells by up-regulating microRNA-423-5p - Haochuan Liu; Bing Chen; Qingsan Zhu (Artificial Cells, Nanomedicine, and Biotechnology)
We, the Editors and Publisher of the journal Artificial Cells, Nanomedicine, and Biotechnology, have retracted the following article:Haochuan Liu, Bing Chen and Qingsan Zhu, (2019). Long non-coding RNA SNHG16 reduces hydrogen peroxide-induced cell injury in PC-12 cells by up-regulating microRNA-423-5p. Artificial Cells, Nanomedicine, and Biotechnology. 47:1, 1444–1451, DOI: 10.1080/21691401.2019.1600530Since publication, the authors noticed that an inappropriate cell line was used. As this error directly impacts the reported results and conclusions the authors alerted the issue to the Editor and Publisher and all have agreed to retract the article to ensure correction of the scholarly record.We have been informed in our decision-making by our policy on publishing ethics and integrity and the COPE guidelines on retractions.The retracted article will remain online to maintain the scholarly record, but it will be digitally watermarked on each page as ‘Retracted’.